929. Recurrent Nocardiosis in Solid Organ Transplant Recipients: An Evaluation of Post-Treatment Prophylaxis. (4th December 2021) - Yetmar, Zachary A; Wilson, John; Beam, Elena
Abstract: Background: Nocardia more commonly causes infection in immunocompromised individuals, notably with a relapse rate of approximately 5%. Solid organ transplant recipients will often receive post-treatment prophylaxis as the underlying immunosuppression is unable to be completely removed. However, data supporting this practice is sparse. We sought to evaluate recurrence of nocardiosis in solid organ transplant recipients, specifically evaluating the role of post-treatment prophylaxis. Methods: We conducted a retrospective cohort study of solid organ transplant (SOT) recipients at our medical center diagnosed with nocardiosis from 2000 through 2020. We included adult SOT recipients who completed their course of Nocardia therapy. Patients were excluded if they had not yet completed therapy, died prior to completing therapy, or there was no post-therapy follow-up. The primary outcome was Nocardia recurrence. Continuous variables were presented as mean or median with interquartile range (IQR). Results: 108 patients meeting inclusion criteria were analyzed. 72 (66.7%) were male and median age was 60 years (IQR 52-65). Most common SOT types were kidney (47.2%), heart (17.6%), kidney-pancreas (11.1%), and lung (11.1%). Median time from transplantation to diagnosis of nocardiosis was 396 days (IQR 154-1071). Most common sites of infection were lung (88.0%), skin (16.7%), brain (13.9%), and blood (6.5%). Multi-organ infection was present in 22.2% and 24.1% were on trimethoprim-sulfamethoxazole (TMP-SMX) prophylaxis at diagnosis. Post-treatment prophylaxis was utilized in 55 (50.9%) patients (Table 1). TMP-SMX was the most common prophylaxis (87.3%; Figure 1). Four patients experienced Nocardia recurrence, 2 of which were receiving TMP-SMX prophylaxis at time of relapse (Table 2). These were dosed as double strength tablet daily and weekly, respectively. Median time from treatment completion to relapse was 255.5 days (range 107-871). Figure 1. Post-Treatment Prophylaxis Regimens for Nocardia in 55 Patients Conclusion: Nocardia recurrence in solid organ transplant recipients is an uncommon occurrence. Double strength daily and weekly TMP-SMX prophylaxis does not appear to be entirely protective and relapse may be dependent upon other factors such as primary treatment length. Further study into the use of post-treatment prophylaxis is warranted. Disclosures: All Authors : No reported disclosures